Morpho-physiological attributes of Blackgram varieties as influenced by planting geometry : Morpho physiological characteristics of Blackgram (Bangladesh Journal of Agriculture, 2025)
The study was carried out at the research field of Sher-e-Bangla Agricultural University, Dhaka during March to June 2021 in Kharif-I season to evaluate the effect of varieties and different plant spacing of blackgram. The trial comprised of three varieties of blackgram viz., V1=BINA mash1, V2=BARI mash2, V3=BARI mash4 and four different plant spacing viz., P1= Broadcast, P2=Paired row (15 cm × 10 cm), P3= Square planting (20 cm × 20 cm) and P4= Row sowing (30 cm × 15 cm). The experiment was laid out in a RCB design with three replications. The results revealed that the blackgram variety BARI mash4 produced the highest seed yield (1.83 t ha-1), whereas BINA mash1 produced the lowest seed yield (1.27 t ha-1). In case of different plant spacing the seed yield ranges between (1.27 -1.83 t ha-1) where maximum seed yield was recorded in spacing of (30 cm × 15 cm). When compared to other treatment combinations, the combination of variety BARI mash4 and 30 cm × 15 cm spacing had an impact on plant growth and yield-contributing characteristics; thus, the results indicated that this combination (30 cm × 15 cm) was suitable for blackgram's maximum growth, seed yield, and yield-contributing parameters.Bangladesh J. Agri. 2024, 49(2): 111-124